A case report:-Ovary penetration by a Multiload-Cu 375 intrauterine contraceptive device (International Journal of Scientific Research and Management (IJSRM), 2016)
Contraception is essential in a developing country like India. Intrauterine Contraceptive Devices (IUCDs) are amongst the most frequently used methods of contraception. The patients with misplaced IUCDs may present with pregnancies or ‘lost strings’ or they may remain asymptomatic.